Nutritive solutions salinized with sodium chloride in the cultivation of crisp lettuce in a hydroponic system (Research, Society and Development, 2021)
The objective of this research was to evaluate the agronomic performance of three crispy lettuce cultivars (Elba, Cristina and Veneranda) grown in a hydroponic-NFT system using nutrient solutions salinized with sodium chloride. The experiment was conducted in a protected environment, at the Center for Agricultural and Environmental Sciences-CCAA of the State University of Paraíba-UEPB Campus-II, located in the rural area of the city of Lagoa Seca-PB, with geographical coordinates: (7° 10′ 15″ S, 35° 51′ 14″ W). The design was in randomized blocks, in a split-plot scheme, the plots consisted of nutrient solutions with different values of electrical conductivity (S2-2.4; S3-2.9; S4-3.4; S5-3.9; S6-4.4 and S7-4.9 dS m-1) and the subplots by different cultivars of curly lettuce (Elba, Cristina and Veneranda), with three replications. The variables evaluated were: Number of leaves per plant-NFP; Total production-PT; Commercial production-PC; Stem diameter-DC; Fresh leaf mass-MFF Dry leaf mass-MSF and Dry stem mass-MSC. Regardless of the variable analyzed, there was no significant interaction between nutrient and cultivar solutions. Regarding the isolated effect of the solution, the largest number of leaves per plant, total and commercial production and fresh leaf mass was obtained with the use of the S1 solution. As for the cultivars, Veneranda presented the highest commercial production, fresh and dry mass of the leaf and dry of the stem, this cultivar also presented the highest average, but without differing from the Elba, when the number of leaves and total production was evaluated.